The Influence of Leadership and Work Environment on the Performance of Employees in the Production Division - Maharani, Devi; Adiwaty, Mei Retno (Journal of Applied Business, Taxation and Economics Research, 2025)
Amid the increasingly intense business competition, a company's ability to adapt dynamically and manage its human resources optimally has become a key factor in achieving long-term excellence and success. Employees are regarded as strategic assets who not only carry out operational tasks but also play an active role in achieving the company’s goals. This study was conducted to analyze the extent to which leadership and work environment influence employee performance at PT. X. The research focuses on the production division, which plays a vital role in supporting the overall business process. A quantitative approach was employed, utilizing Partial Least Square (PLS) analysis, and the sample was determined using a saturated sampling method, involving all 62 employees in the production division. The findings indicate that leadership style has a constructive impact on employee performance, while the work environment also contributes positively to enhancing employee performance.